Electrosprayed polymeric nanobeads and nanofibers of modafinil: preparation, characterization, and drug release studies - Adibkia, Khosro (Bioimpacts, 2019)
[Image: see text] Introduction: Modafinil (MDF) is used orally for the treatment of attention-deficit/hyperactivity disorder and narcolepsy. It holds low solubility and high permeability; therefore, improving its dissolution properties by preparing nanoformulations can be a promising approach to enhance its oral absorption. Our aims were to prepare and characterize MDF-Eudragit® RS100 (MDF-ERS) nanoparticles by electrospray technique. Methods: Electrosprayed nanoparticles were fabricated by varying MDF to ERS ratios and concentrations. The formulations were characterized by scanning electron microscopy (SEM), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and Fourier-transform infrared spectroscopy (FTIR). Release studies were performed on nanoparticles, physical mixtures, and raw MDF. The release data were fitted to different models to understand the mechanism of the drug release. Results: Electrospraying of MDF and ERS solution resulted in the preparation of nonobeads or nanofibers, and the particulate characteristics of the obtained products were largely controlled by the polymer amount in the solution. PXRD and thermal analyses showed that MDF was an amorphous phase in the structures of nanoparticles. Using FTIR, no interaction was observed between MDF and ERS in nanoparticles. Nanoparticles showed biphasic release profiles and the order of dissolution rates was: nanofibers>MDF>nanobeads. The well-fitted model was Weibull model, indicating a Fickian diffusion as the main mechanism of release. Conclusion: The results suggest that by optimization of variables such as solution concentration of MDF-ERS nanofibers and nanobeads with higher dissolution rates can be made by electrospray. Electrospray deposition as a simple, continuous, and surfactant free method is an excellent choice for preparation of drug loaded polymeric nanoparticles.